Phenotypic variation in arid and semi-arid zones of southern South America: the case of Senna series Aphyllae (Fabaceae, Caesalpinioideae) - Robbiati, Federico Omar; Amarilla, Leonardo D.; Anton, Ana Maria Ramona; Fortunato, Renee Hersilia (Oxford University Press, 2021)
Senna series Aphyllae includes xeromorphic shrubs and subshrubs that occur in three different biogeographic subregions in arid and semi-arid habitats of southern South America. The series provides a good opportunity to understand better the relationship among geographical, climatic, and morphological variation in different taxa. Moreover, in this group the specific and varietal delimitation is still problematic due to the high morphological variation within and among taxa. Statistical analyses of climatic and morphological data and geographical distribution were used to understand the patterns of morphological variation among 394 individuals and to clarify the taxonomic delimitation of entities that belong to series Aphyllae. Senna acanthoclada and S. nudicaulis were segregated from each other and from the remaining taxa; the three recognized varieties of the S. aphylla complex were delimited; S. spiniflora was well-delimited and S. crassiramea and S. rigidicaulis were overlapping; S. pachyrrhiza was not differentiated from S. aphylla. Ecological niche modelling showed several areas of contact and a large overlap of suitable conditions for several species. The results of this work revealed that most morphological variability is associated with different environmental conditions. This phenotypic plasticity may be caused by the presence of different environments with climatic factors in the South American Transition Zone, Chaco, and northern region of Central Patagonia province.